Communication Pattern Family and Adolescent Mental Health for Strawberry Generation - Dyva Claretta; Farikha Rachmawati; Atjih Sukaesih (GoAcademica Research & Publishing, 2022)
Health is not only related to health physique only but also mental health. Research results prove that teenagers 16-24 years old are period critical for Indonesian adolescents' mental health. The research objective is to know and study by deep about the application of pattern communication family to adolescent mental health. Use method qualitative with approach phenomenology. The object of study is teenagers who have disturbed mental health in the city of Surabaya. Data collection techniques using interviews in-depth and data analysis using stages Miles, Hubberman & Saldana. Validity study researched use triangulation. Research results show that pattern communication authoritarian in the family is the main factor teenagers have disturbance mental health. This is because teenagers feel depressed and inclined no have pattern communication democratic in their families. Implication teenager characters are closed, and not can express feelings. The research results are also useful and become a reference for educators as well as parents in repair pattern communication with Strawberry Generation.